Navigating loyalty and trust in the skies: The mediating role of customer satisfaction and image for sustainable airlines - Irfan Hameed; Rajat Subhra Chatterjee; Bibi Zainab; Ang Xian Tzhe; Lim Shea Yee; Kamran Khan (Sustainable Futures)
This study aims to pinpoint the key factors influencing customer loyalty and trust within the airline industry. The study investigates the impact of service quality (assessed through the SERVQUAL model), pricing fairness, and perceived value on passengers' loyalty and trust in airlines. Additionally, the research delves into the mediating influences of passenger satisfaction and airline image in this domain. The data has been collected from the passengers who have lately used air transport to travel. The respondents included 400 passengers and were targeted using a purposive sampling technique. The findings reveal a significant positive correlation between service quality, price fairness, and perceived value, as well as passengers' loyalty and trust in airlines. Furthermore, we discovered that customer satisfaction and the airline's image played crucial roles as mediators, enhancing our understanding of the core mechanisms driving loyalty and trust formation among passengers.